Electrospinning parameters evaluation of PVDF-ZnO/Ag2CO3/Ag2O composite nanofiber affect on porosity by using response surface methodology. (2021) - Rosman, Nurafiqah; Wan Salleh, Wan Norharyati; Jamalludin, Mohd Riduan; Adam, Mohd Ridhwan; Ismail, Nor Hafiza; Jaafar, Juhana; Harun, Zawati; Ismail, Ahmad Fauzi
Abstract: The electrospinning process is a very important technique for fabricating polymeric nanofibers by applying external electrostatic forces. This study reports on the modeling of the electrospinning process of polyvinylidene fluoride (PVDF) and the immobilized ZnO/Ag2 CO3 /Ag2 O using response surface methodology (RSM) based on the central composite design (CCD). The individual and interaction effects of the most effective variables, such as applied voltage (6.5, 8 and 9.5 kV), nozzle-collector distance (10, 12.5 and 15 cm) and ZnO/Ag2 CO3 /Ag2 O photocatalyst concentration (0.1, 0.8 and 1.5 g), have been evaluated on the porosity response of the nanofiber. The analysis of variance (ANOVA) confirmed that the spinning voltage was the main variable affecting the average porosity of the composite PVDF nanofiber. The regression coefficient between the variables and the mean porosity (R2 = 0.8321) indicates acceptable evaluation of experimental data by quadratic polynomial regression.